Internet connectivity disruption in Moldova (Moldova) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Moldova. Data sourced from IODA.
Network Disruption Incident ID: MD-2026-0024. Severity: critical. Confidence: 70%